Ontologia e lógica na filosofia especulativa de Hegel - Wesan, Leandro Alberto Xitiuk (2014)
This dissertation aims to present and discuss the speculative philosophy of Hegel from the problem of the opposition between subject and object. This problem refers to the possibility of philosophy to be right and true knowledge of reality. The philosophy in modernity as Hegel explains is characterized by the question of the possibility of knowledge, i.e. the possibility of perfect conformity between consciousness and the thing, because only if the opposition between subject and object is dissolved, the philosophy can be re-stated as absolute science of reality. Hegel in his speculative philosophy identifies logic and ontology at the task of resolving the dualism between thought and thing, dualism which limited the possibility of absolute knowledge of reality, namely, according to Hegel, knowledge that is presented as syllogistic synthesis between subject, object and method. Thus, speculative philosophy is characterized according to the deployment of the Hegelian system as a meeting of logic and ontology. In modernity, as Hegel exposes the speculative philosophy was seen as lacking in scientific foundation. Hegel refers to this perspective as the view that metaphysics acquired at this time, namely, to be absent from certain speculation. However, speculative philosophy developed in Hegel's system, aims to give back to philosophy and its universal real significance, the extent that exceeds and surpasses the subjective rationality and critique of modern philosophy about the possibility of knowledge. Hegel aims to develop the concept of logic beyond the formalism that this science is. The foundation to accomplish this purpose lies in building a new concept of thought. Hegel develops the concept of thinking beyond their uniquely subjective dimension, the extent that demonstrates the objectivity of thought in its design of speculative logic. In this sense, Hegel perceives the need for objective logic support a conception of thought that is not driven by its formal determination that is presented in the form of the self, the subjective consciousness. The possibility of knowledge, a task that was assumed by speculative philosophy to try to advance the philosophy of his epistemological crisis, requires abandoning the shape of the finite consciousness as I go to infinity and thought content. In speculative philosophy, Hegel promises to lead to perfectly logical nature of philosophy, by identity between ideality and reality, which is the main problem of Hegelian philosophy, the extent that such identification takes amazement determines the question of knowledge in philosophy modern: thought and concept were considered to Hegel's philosophy as abstract idealizations, which remained in the realm of subjective representation; in Hegelian philosophy pure thinking and conceptualizing are analogous to real-world knowledge. In his conclusion Hegel's philosophy aims to be the dialectical exposure, so the development, that is, the coming-to-be, the perfect idea, namely, the absolute.